Distribution of Mimosa diplotricha C. Wright nil invasive weed in relation to other herbaceous weeds in Agrarian ecosystems of Ibadan, Nigeria (2017)
Mimosa diplotricha is an invasive weed whose spread can have negative impacts on plant biodiversity and agriculture.''In this study, a floristic survey was used to assess the distribution of Mimosa diplotricha in relation to other weed species in Ibadan, Nigeria. Florisiic survey was conducted using Jm x lin quadrat at 0.5 km intervals on transects along major roads of six purposively selected agrarian ureas based on prevalence oj Mimosa diplotricha, frdm Ibadan metropolis to: Alai jo, Akanran, lyana-Offa, Idi-Ayunre, hldo and Susa. The entire arpas are within 7° 14-7°30'N; 3°48'-4°04 E and altitude 127-261 in asl). The Relative Importance Values (RIV, %), relative density and relative, frequency, diversity indices {Species richness (S), Shannon-Wiener (11) and Evenness (J)} were determined. Eighty-six pHint species from twenty-eight families were enumerated. The RIV of Mimosa diplotricha was highest in all areas: 17.1 (Susa), 22.5 (Alcufo), 3L5 (Idi-Ayunre), 23.3 (lyana -Ojfa), 21.4 (Iddo), 36.0 (Akanran). While, the least RIV ranged from 0.31 (Luffa cylindrica; Sasa) to 0.97fCommelina erecta; Iddo). The Species richness (S), Shannon-Wiener (H) and Evenness (J) indices, in the areas were: 56.0, 3.1, 0.4 (Sasa); 31.0, 2.6, 0.4 (Alcufo); 44.0, 2.5, 0.3 (TdiAyunre); 40.0, 2.7, 0.4 (lyana Ojfa); 29.0, 2.6, 0.5 (Iddo) and 35.0, 2.0 and 0.2 (Akanran), respectively. The'high diversity indices revealed random distribution of species. However, high RIV values of Mimosa diplotricha in all surveyed axes showed that it is fast becoming the dominant weed species in Ibadan and may be a threat to